FENOMENOLOGI PERAN EDUKATIF GURU DALAM MENANAMKAN NILAI ISLAM MELALUI KEGIATAN SEHARI HARI DI TADIKA AL FIKH ORCHARD AWANI BANGI - Siera Ayudia; Hasrian Rudi Setiawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the educational role of teachers in instilling Islamic values through daily activities at Tadika Al Fikh Orchard Awani Bangi. The focus of the study includes the implementation of the teachers’ educational role, the methods used to integrate Islamic values into daily learning activities, the factors influencing effectiveness, and the challenges faced along with the strategies applied to overcome them. This research employed a qualitative approach with a phenomenological design to explore teachers’ lived experiences in the process of value internalization. The research subjects consisted of teachers as the main informants and students aged 4–6 years as participants. Participatory observation, in-depth interviews, and documentation were used to gather data. The Miles and Huberman model, which involves data reduction, data display, and conclusion drawing, was used to analyze the data. Triangulation of sources, triangulation of techniques, and extended engagement were used to guarantee the authenticity of the data. The findings indicate that Islamic values were integrated into daily habituation activities such as prayer practices, teacher role modeling, discipline, responsibility, social interaction, and Islamic-themed educational games. Continuous habituation and positive reinforcement effectively shaped students’ religious character despite challenges related to diverse student characteristics, limited instructional time, and limited school–family continuity.